Relationship of Study Skills and Academic Achievement of University Students - Alia Siraj; Syed Afzal Shah; Sarfaraz Khan (Journal of Management Practices, Humanities and Social Sciences, 2021)
The topic of research was the relationship between study skills and academic achievement of university students. The study's research questions were; (i) what types of study skills are possessed by the university students? (ii) How do study skills vary among students in terms of gender, specialization, and levels of study? (iii) Is there any relationship between study skills and academic achievement of university students? The current study followed the non-experimental method and cross-sectional research design and was conducted at the university level. The undergraduate students were targeted in this research. Since most studies are conducted at the school level, the sample of study incorporated 400 BS students by using a strati